Curcumin, myrecen and cineol modulate the percentage of lymphocyte subsets altered by 2,3,7,8-Tetracholorodibenzo-p-dioxins (TCDD) in rats - Ciftci, Osman; Tanyildizi, Sadettin; Godekmerdan, Ahmet (Sage Publications Ltd, 2011)
The aim of this study was to investigate the toxic effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a persistent environmental pollutant, on the percentage of T-cell subsets and B-lymphocyte and effectiveness of curcumin, beta-myrcene (myrcene) and 1,8-cineole (cineol) on this toxicity in rats. Rats (n = 112) were divided randomly into 8 equal groups. One group was kept as control and given corn oil as carrier. TCDD was orally administered at the dose of 2 mu g/kg/week. Curcumin, myrcene and cineol were orally administered by gavages at the doses of 100, 200 and 100 mg/kg/day, respectively, dissolved in corn oil with and without TCDD. The blood samples were taken from half of the rats on day 30 and from the rest on day 60 for the determination of lymphocyte subsets (CD3(+), CD4(+), CD8(+), CD161(+), CD45RA, CD4(+)CD25(+) and total lymphocyte). The results indicated that although TCDD significantly (p < 0.05) decreased the percentage of CD3(+), CD4(+), CD161(+), CD45RA, CD4(+)CD25(+) and total lymphocyte, it caused a significant increase in the percentage of CD8(+) cells. In contrast, curcumin, myrcene and cineol significantly decreased CD8(+) cells levels but increased CD3(+), CD4(+), CD161(+), CD45RA, CD4(+)CD25(+) and total lymphocyte cells populations. The beneficial effects of curcumin, myrcene and cineol and the toxic effects of TCDD were increased at day 60 compared to day 30. In conclusion, curcumin, myrcene and cineol showed immunomodulatory effects and eliminated TCDD-induced immune suppressive effects in rats.
Keywords: 2, 3, 7, 8-TCDD; curcumin; myrcene; cineol; T-cell subsets; B cells